HUBUNGAN HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG COVID-19 DENGAN PERILAKU PENCEGAHAN COVID-19 - Suroso; Heni Purwanti; Yunita Fajriati (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction coronavirus Disease 2019 (COVID-19) is currently a serious world problem with the number of cases which are always increasing every day. It is known that the origin of this virus came from Wuhan, China. Found at the end of December 2019. Globally until 21 August 2020 cases of COVID-19 in the world there were 22,256,220 confirmed cases. Knowledge about COVID-19 is very important for the public to have so that people are able to make decisions in behaving appropriately in order to break the chain of COVID-19 transmission. The purpose of this study was to determine the relationship between the level of public knowledge about COVID-19 and the prevention behavior of COVID-19 RT 002 RW 005 Perigi Baru District, Pondok Aren, South Tangerang city. This study is an observational analytic study with a cross sectional design. The research measurement tool using a questionnaire. The population in this study were people aged 17-45 years in RT 002 RW 005, Perigi Baru District, Pondok Aren, South Tangerang city, which were 249 respondents with a total sample of 66 respondents using a quota sampling technique. Based on the research , the results of the analysis using the chi square test obtained a p value of 0.000, which means that there is a relationship between the level of public knowledge about COVID-19 and the prevention behavior of COVID-19 RT 002 RW 005, Perigi Baru District, Pondok Aren, South Tangerang city.